Oral human cytomegalovirus prevalence and its relationships with periodontitis and Porphyromonas gingivalis in Japanese adults: a cross-sectional study (Journal of Applied Oral Science, 2021)
Objective: This study aimed to clarify the association between oral human cytomegalovirus (HCMV) and periodontitis in Japanese adults. Methodology: In total, 190 patients (75 men and 115 women; mean age, 70.2 years) who visited Hiroshima University Hospital between March 2018 and May 2020 were included. Oral rinse samples were taken to examine the presence of HCMV DNA using real-time polymerase chain reaction (PCR). P. gingivalis was detected by semi-quantitative PCR analysis. Results: HCMV DNA was present in nine of 190 patients (4.7%). There were significant associations between HCMV presence and the presence of ≥4-mm-deep periodontal pockets with bleeding on probing (BOP) (P<0.01) and ≥6-mm-deep periodontal pockets with BOP (P=0.01). However, no significant relationship was observed between HCMV presence and periodontal epithelial surface area scores. Logistic regression analysis revealed that the presence of ≥4-mm-deep periodontal pockets with BOP was significantly associated with HCMV (odds ratio, 14.4; P=0.01). Propensity score matching was performed between patients presenting ≥4-mm-deep periodontal pockets with BOP (i.e., active periodontitis) and patients without ≥4-mm-deep periodontal pockets with BOP; 62 matched pairs were generated. Patients who had ≥4-mm-deep periodontal pockets with BOP showed a higher rate of HCMV presence (9.7%) than those who lacked ≥4-mm-deep periodontal pockets with BOP (0.0%). There was a significant relationship between HCMV presence and ≥4-mm-deep periodontal pockets with BOP (P=0.03). A significant relationship was found between HCMV/P. gingivalis DNA presence and ≥4-mm-deep periodontal pockets with BOP (P=0.03). Conclusions: Coinfection of oral HCMV and P. gingivalis was significantly associated with active periodontitis. Moreover, interactions between oral HCMV and P. gingivalis may be related to the severity of periodontal disease.